2022
DOI: 10.3390/signals3010009
|View full text |Cite
|
Sign up to set email alerts
|

Smart Clothing Framework for Health Monitoring Applications

Abstract: Wearable technologies are making a significant impact on people’s way of living thanks to the advancements in mobile communication, internet of things (IoT), big data and artificial intelligence. Conventional wearable technologies present many challenges for the continuous monitoring of human health conditions due to their lack of flexibility and bulkiness in size. Recent development in e-textiles and the smart integration of miniature electronic devices into textiles have led to the emergence of smart clothin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 120 publications
0
18
0
Order By: Relevance
“…2,3 This could potentially drastically change the way athletes are trained and monitored physiologically, ultimately improving their performance during games. 1,4,5…”
Section: Introductionmentioning
confidence: 99%
“…2,3 This could potentially drastically change the way athletes are trained and monitored physiologically, ultimately improving their performance during games. 1,4,5…”
Section: Introductionmentioning
confidence: 99%
“…Various wearable devices have different functions according to the needs of different industries such as changing the way of work in various industries, improving people's work efficiency, or generating new ways of working [2]. From the recent research literature on the development of wearable devices, in the next few years, wearable devices will also bring astonishing industrial value; there will also be more and more different applications [3], such as smart wristbands, smart rings, smart clothes, smart pants, etc. To cooperate with ergonomics to achieve the best fit, or to measure the vital signs on the body surface, wearable devices must be attached to the torso, arms, legs, head, etc., so that part of the shape will be curved in order to achieve the best fit [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, medical personnel need to wear various medical protective equipment, including medical protective masks, masks, protective clothing, and gloves. This medical protective equipment can be transformed into wearable devices by adding electronic equipment [3,4]. One of the important items is to join a wireless…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several types of smart sportswear are in development or on the market to improve performance and health of athletes. Due to the many sources the latest brief reviews of smart clothing applications can be found in [11][12][13].…”
Section: Introductionmentioning
confidence: 99%